Effect of statin treatment on circulating malondialdehyde concentrations: a systematic review and meta-analysis. (July 2019) - Zinellu, Angelo; Paliogiannis, Panagiotis; Usai, Maria Franca; Carru, Ciriaco; Mangoni, Arduino A.
Background: The effect of statins on oxidative stress markers, such as malondialdehyde (MDA), is still a matter of debate. We sought to address this issue by conducting a systematic review and meta-analysis of published data on the effect of statin treatment on systemic MDA concentrations. Methods: A literature search was conducted on MEDLINE / PubMed, ISI Web of Sciences and Scopus . Data were pooled using a random-effects model. Results: A total of 35 studies assessing MDA concentrations before and after statin treatment in 1512 participants (mean age 53.6 years, 48.7% males) were identified. Extreme between-study heterogeneity was observed (I 2 = 96.0%, p < 0.001). Pooled standardized mean difference (SMD) showed a significant reduction in plasma MDA concentrations after treatment (SMD = −1.47 µmol/l, 95% confidence interval = −1.89 to −1.05 μmol/l; p < 0.001). Similarly, a subgroup analysis of 10 studies that also included a placebo group showed a significant reduction in plasma MDA concentrations with statins (−1.03 μmol/l, 95% confidence interval = −1.52 to −0.29 μmol/l; p = 0.036). Conclusions: This systematic review and meta-analysis showed that statin treatment significantly reduces systemic MDA concentrations. However, the results should be interpreted with caution because of extreme between-study heterogeneity, which warrants further intervention studies.